2018
DOI: 10.1111/jocd.12676
|View full text |Cite
|
Sign up to set email alerts
|

Platelet rich plasma for photodamaged skin: A pilot study

Abstract: A simple method of PRP preparation offers modest benefit in treating the effects of skin aging and photodamage. Future research studies should alter our methods using a stepwise approach to optimize the treatment of aging facial skin with PRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…To the best of our knowledge, only two studies have used the FACE-Q to evaluate patient-reported outcomes following use of PRP or PRF monotherapy for facial rejuvenation. 43,44 In one study, Lee and colleagues showed improvement in participant satisfaction with overall facial appearance and cheeks following a single injection of PRF 43 while in the other study Nacopoulos and colleagues that reported an improvement in the satisfaction with skin questionnaire following several sessions of injectable PRF treatment. 44 To our knowledge, the clinical use of injectable PRF for facial aesthetics has only been previously reported in a single study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only two studies have used the FACE-Q to evaluate patient-reported outcomes following use of PRP or PRF monotherapy for facial rejuvenation. 43,44 In one study, Lee and colleagues showed improvement in participant satisfaction with overall facial appearance and cheeks following a single injection of PRF 43 while in the other study Nacopoulos and colleagues that reported an improvement in the satisfaction with skin questionnaire following several sessions of injectable PRF treatment. 44 To our knowledge, the clinical use of injectable PRF for facial aesthetics has only been previously reported in a single study.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the low baseline score for skin adverse effects (29 of 100), the lack of a statistically significant improvement is not unexpected. To the best of our knowledge, only two studies have used the FACE‐Q to evaluate patient‐reported outcomes following use of PRP or PRF monotherapy for facial rejuvenation 43,44 . In one study, Lee and colleagues showed improvement in participant satisfaction with overall facial appearance and cheeks following a single injection of PRF 43 while in the other study Nacopoulos and colleagues that reported an improvement in the satisfaction with skin questionnaire following several sessions of injectable PRF treatment 44 …”
Section: Discussionmentioning
confidence: 99%
“…Half of the acne scarring studies (4/8 = 50%) were classified as high quality, providing results from placebo-controlled, randomized, and blinded trials (Table 3). [48][49][50][51] Conversely, 57% (8/14) of aging facial skin studies [69][70][71][72][73][74][75][76] and 67% (6/9) of facial procedure studies [63][64][65][66][67] were graded as low-quality and moderatequality studies, respectively (Table 3).…”
Section: Other Aesthetic Applications Of Prpmentioning
confidence: 99%
“…Clinical use of PRP injections has gained traction in plastic surgery, 12 maxillofacial surgery, 13 wound healing, 14 and dermatology. 15 In the practice of sports medicine, PRP injections have been used in the treatment of lateral epicondylitis, showing reduced rates of conversion to surgical treatment from medical management, 16 as well as marked improvement in visual analog scale (VAS) pain scale and tendon appearance on magnetic resonance imaging (MRI). 17 Furthermore, PRP has been shown to provide relief from pain and inflammation associated with OA, making it a therapeutic treatment in the management of OA.…”
mentioning
confidence: 99%